Edukasi Pertolongan Pertama Tersedak Dengan Teknik Heimlich Maneuver Pada Siswa MTS Al-Ihsan - Hafizhah Nur Istiqomah; Kharisma Wahyu Widodo; Nabilla Dyva Chiendytya; Nora Herawati; Bagas Biyanzah Drajad Pamukhti (PPNI UNIMMAN, 2024)
Choking is still a concern today, as it is the fourth leading cause of unintentional death. Choking often occurs in infants and children, most of whom are 14 years old. From the results of interviews, it is known that students' knowledge related to handling choking with the heimlich maneuver technique is still lacking. At the service partner, MTS Al-Ihsan Cepogo, Boyolali, education has also never been carried out regarding choking management, especially with the heimlich maneuver technique. The purpose of this community service is to increase students' knowledge and skills related to choking handling using the heimlich maneuver technique. The community service method through educational activities and demonstrations showed an increase in student knowledge by 88%.